An Examination of the Productivity Decline in the Construction Industry - Stokes, H. Kemble (The Review of Economics and Statistics, 1981)
THE decline in the rate of productivity growth that has occurred in the private nonfarm economy during the last decade has been particularly acute in the construction industry. Between 1950 and 1968, labor productivity in the private nonfarm sector rose at an annual rate of 2.4%; between 1968 and 1978 the yearly rise was only 1.2%. In the construction industry productivity rose by about 2.4% annually between 1950 and 1968, but has declined by 2.8% annually since then. This paper addresses seven possible explanations for these trends in construction industry productivity. These include (a) the measurement of real output, (b) shifts in the composition of construction industry output, (c) changes in capital per worker, (d) demographic changes in the workforce, (e) economies of scale, (f) regional shifts, and (g) changes in work rules or practices. The results are disconcerting. Only a small portion of the deterioration in productivity is explained by these factors. In all of the presentations below, rates of growth are measured from 1950 to 1968 and from 1968 to 1978, except where precluded by the unavailability of data. Labor productivity reached a peak in 1968 and thus this date serves as a convenient point to split the historical period. Prior to 1968 there were only a few years, depending on the measure used, in which productivity declined; after 1968 there were only one or two years in which productivity increased. The problem of declining productivity cannot be isolated to a particular year or two, but rather has persisted almost without exception for the last decade. Measures of growth in labor productivity are displayed in table 1. The measure of output in each case is real value added. While there are differences between these rates of productivity growth, they are relatively minor. This suggests that productivity differences due to (a) the distinction between hours worked and hours paid, (b) the distinction between employees and all persons, which also includes proprietors and unpaid family workers, and (c) the distinction between employment and hours, reflecting changes in the number of hours worked per employee, are not particularly important in explaining the decline in construction productivity in the last decade. In this sense the problem is not how to measure productivity.